Fulfillment of Prisoners’ Rights to Occupational Safety Guarantees and Work-Performance Premiums: An Empirical Study at the Class III Penitentiary of Lhoknga - Pidiea, Kanasa Putri; Aguswandi, Putra; ‘Aidy, Zul; Rahmah, Siti; Megawati, Cut (Yayasan Abdurrauf Cendekia Nusantara, 2025)
Article 9 letter j of Law Number 22 of 2022 on Corrections stipulates that every inmate is entitled to occupational safety assurance, wages, or work?performance premiums. This provision has not been fully implemented at the Class III Lhoknga Correctional Facility, particularly regarding work protection and fair remuneration for inmates participating in vocational activities. This study aims to explain the mechanism for fulfilling inmates’ rights to occupational safety assurance and the provision of wages or work premiums, identify the obstacles encountered in its implementation, and analyze the efforts undertaken to address these challenges. The research employs an empirical juridical approach through field observations and interviews to assess the effectiveness of statutory implementation within correctional practice. The findings indicate that the fulfillment of inmates’ rights to occupational safety and the distribution of wages or work premiums has not been optimal. Several work activities are not supported by adequate safety standards, and the remuneration provided does not yet meet the principles of fairness mandated by the relevant regulations. [Pasal 9 huruf j Undang-Undang Nomor 22 Tahun 2022 tentang Pemasyarakatan menetapkan bahwa setiap narapidana berhak memperoleh jaminan keselamatan kerja, upah, atau premi hasil kerja. Ketentuan ini belum sepenuhnya terimplementasi di Lembaga Pemasyarakatan Kelas III Lhoknga, khususnya terkait perlindungan kerja dan imbalan yang layak bagi narapidana yang mengikuti program pembinaan kerja. Penelitian ini bertujuan menjelaskan mekanisme pemenuhan hak atas jaminan keselamatan kerja serta pemberian upah atau premi, mengidentifikasi kendala yang dihadapi dalam pelaksanaannya, dan menganalisis upaya yang ditempuh untuk mengatasi hambatan tersebut. Penelitian menggunakan pendekatan yuridis empiris melalui observasi dan wawancara untuk menilai efektivitas penerapan regulasi dalam praktik pemasyarakatan. Temuan penelitian menunjukkan bahwa pemenuhan hak narapidana terkait jaminan keselamatan kerja dan pemberian upah atau premi belum berjalan optimal. Beberapa kegiatan kerja belum disertai standar keselamatan yang memadai, sementara pemberian upah atau premi belum memenuhi prinsip kelayakan sebagaimana diamanatkan oleh peraturan perundang-undangan.]